PRIMARY RETROGRADE TIBIAL-PEDAL ACCESS IN PATIENTS WITH CRITICAL LIMB ISCHEMIA - Tajibayev Talgat Kadyralievich; Baubekov Alzhan Alkeshevich; Nussipakynov Arman Kydyrkulovich; Nurmaganbet Samal Timorovna (Актуальные проблемы теоретической и клинической медицины, 2024)
The most common complications after percutaneous vascular interventions are complications at the site of access. The use of retrograde tibial-pedal access could reduce the risks of significant complications at the puncture site compared to traditional femoral access. Purpose: In this study, we aimed to determine the efficacy and safety of primary tibial-pedal access for revascularization of chronic total occlusion of the femoral-popliteal and infrapopliteal segments in patients with critical lower limb ischemia. Materials and Methods: We conducted a retrospective analysis of 18 patients from January 2022 to August 2024. Patients were selected according to the following criteria: patients with categories 3, 4, 5 according to the Rutherford classification and stages 3,4 according to the Fontaine classification; femoropopliteal (FP) lesion with or without involvement of the infrapopliteal (IP) segment; the presence of blood flow in one or more distal or pedal segments of the main arteries of the leg and foot; informed consent of patients for the intervention. Results: The overall procedural success rate of the intervention was 100%. The average age of patients was 74±5 years. The majority of the subjects were women (66.7%). Comorbidities such as diabetes mellitus (66.7%), arterial hypertension (55.5%), coronary artery disease (38.9%), and hyperlipidemia (77.8%) were diagnosed. The artery of choice in the majority of cases was the anterior tibial artery 13 (72.2%) Balloon angioplasty combined with stent placement was performed in 14 cases (77.8%). Minor bleeding at the puncture site occurred in 1 case (5.5%). There were no signs of major bleeding, hematomas, MALE, MACE, or death in any case. All patients experienced relief of pain of ischemic origin. Conclusion: Retrograde tibial-pedal access is technically easier with a tendency to fewer complications. This technique can be used as a primary procedure or as an alternative to antegrade femoral access in complex patients with a high risk of hematoma formation.